Cloning and Expression of ORF124 Koi Herpesvirus as a Vaccine - ., Murwantoko; Pratiwi, Rarastoeti; Kawaichi, Masashi (Universitas Gadjah Mada, 2012)
Koi herpesvirus (KHV) which also known as Cyprinid herpesvirus 3 (CyHV-3), Koi herpes-like virus, and carp interstitial nephritis gill necrosis virus (CNGV), caused signifi cant morbidity and mortality in koi and common carp (Cyprinus carpio). The case fatality rate of this disease is 80–100%. Glycoprotein has been used for vaccine development as sub unit vaccine against viruses. The aim of this research was to clone and express membrane glycoprotein ORF124 KHV as a candidate of recombinant vaccine. ORF124 KHV gene was successfully cloned into pBSKS and sequenced. Result showed that ORF124 KHV (isolate from Indonesia) had 100 % similarity with Cyprinid herpesvirus 3 strain TUMST1 (from Japan), 99% similarity with Koi herpesvirus strain KHV-U (from USA) and Koi herpesvirus strain KHV-I (from Israel). Prediction analysis of T and B cell epitopes showed that ORF124 KHV protein had 14 and 11 T cell epitopes (IAd, Rothbard/Taylor pattern),and had 10 B cell epitopes, suggested that the protein can be used as a vaccine candidate. ORF124 gene has been expressed in Escherichia coli under pET32-a(+)vector.